2015
DOI: 10.1080/15313204.2014.954739
|View full text |Cite
|
Sign up to set email alerts
|

Missing the Mark: The Image of the Social Work Profession in an African-American Community

Abstract: This exploratory study used a project-developed questionnaire to examine the perceptions of members of an African-American community ( N = 102) regarding the social work profession and its commitment to issues pertinent to African-Americans. The results suggested that while the African-American respondents felt that social workers could be a source of help, a considerable amount of the respondents reported that they did not see social workers as being helpful or sensitive to the needs of African-Americans. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 24 publications
1
3
0
1
Order By: Relevance
“…The profession's public image has been debated and studied repeatedly since its inception (Gibelman, 1999), with some studies indicating the public's positive perception of social work (LeCroy & Stinson, 2004) and some indicating a negative public perception (Condie et al, 1978). Most studies of public perception support the findings of this study in that they have found that the public had a vague or narrow understanding of the profession of social work (Dennison, Poole, & Qaqish, 2007;Jones, Vela, Vang, & Walden, 2006;Williams, Simon, & Bell, 2015;Zugazaga, Surette, Mendez, & Otto, 2006). The problems that community practice social workers face related to the perception of social work as a narrow field with some negative connotations likely requires a concerted effort to change the image of social work.…”
Section: Discussionsupporting
confidence: 73%
“…The profession's public image has been debated and studied repeatedly since its inception (Gibelman, 1999), with some studies indicating the public's positive perception of social work (LeCroy & Stinson, 2004) and some indicating a negative public perception (Condie et al, 1978). Most studies of public perception support the findings of this study in that they have found that the public had a vague or narrow understanding of the profession of social work (Dennison, Poole, & Qaqish, 2007;Jones, Vela, Vang, & Walden, 2006;Williams, Simon, & Bell, 2015;Zugazaga, Surette, Mendez, & Otto, 2006). The problems that community practice social workers face related to the perception of social work as a narrow field with some negative connotations likely requires a concerted effort to change the image of social work.…”
Section: Discussionsupporting
confidence: 73%
“…Similarly, our findings could also be associated with a limited understanding of the social work profession and, in particular, social workers’ role in mental health care (LeCroy & Stinson, 2004; Williams et al, 2015). The overwhelming association of social work with child welfare and homeless services, two highly stigmatized populations, may, at worst, increase the perceived stigma associated with the profession as a whole and, at best, limit the public’s perception of social workers as a potential source of behavioral health treatment.…”
Section: Discussionmentioning
confidence: 82%
“…In a 2004 nationally representative telephone survey, respondents viewed social work positively overall, but believed them to be less effective in treating behavioral health problems than psychologists or psychiatrists and most appropriate in roles related to child protection (LeCroy & Stinson, 2004). Numerous studies have found social workers to be the professional least likely to be visited for a behavioral health problem (Condie, Hanson, Lang, Moss, & Kane, 1978; Fall, Levitov, Jennings, & Eberts, 2000; Hardy, 2014; Williams, Simon, & Bell, 2015) and in two studies of African Americans, religious leaders were preferred (Hardy, 2014; Williams et al, 2015). It might also have been the case that individuals received help from a social worker for a behavioral health problem, but within the context of a broader health issue or stressful life event (Gadalla, 2007; Price, 2010; Simning et al, 2010; Taylor, Neighbors, & Broman, 1989).…”
Section: Use Of Social Workers For a Behavioral Health Problemmentioning
confidence: 99%
“…To understand what they consider we need to know about them and respond to their priorities is the aim of social work practice with multicultural communities.Why, then, is there a disconnect between social work and multicultural communities? A survey of an African American community revealed overwhelming agreement that social workers can be a great source of comfort to people in times of need (Williams, Simon, & Bell, 2015), consistent with perceptions of the general population (LeCroy & Stinson, 2004). Yet there was significantly less agreement that social workers were sensitive to their needs.…”
mentioning
confidence: 88%